Emerging Therapies in Neurorehabilitation II - Pons, José L.; Raya, Rafael; González, José (Biosystems & Biorobotics, 2016)
This book reports on the latest technological and clinical advances in the field of neurorehabilitation. It is, however, much more than a conventional survey of the state-of-the-art in neurorehabilitation technologies and therapies. It was written on the basis of a week of lively discussions between PhD students and leading research experts during the Summer School on Neurorehabilitation (SSNR2014), held September 15-19 in Baiona, Spain. Its unconventional format makes it a perfect guide for all PhD students, researchers and professionals interested in gaining a multidisciplinary perspective on current and future neurorehabilitation scenarios.  The book addresses various aspects of neurorehabilitation research and practice, including a selection of common impairments affecting CNS function, such as stroke and spinal cord injury, as well as cutting-edge rehabilitation and diagnostics technologies, including robotics, neuroprosthetics, brain-machine interfaces and neuromodulation.